Automated High-Throughput Live Cell Monitoring of Scratch Wound Closure - Kevin Schmidt; Dominik Lerm; Arne Schmidt; Nicholas Dickel; Jan Fiedler; Thomas Thum; Meik Kunz (Biomedical Engineering and Computational Biology)
Background: Angiogenesis and regenerative wound healing rely on the promotion of distinct endothelial cell phenotypes exhibiting increased migratory capacity. Monitoring of these hallmark events in vitro is invaluable for discovering novel therapeutics. However, respective methods often lack a high-throughput character or accurate analysis tools, which are essential for effective screening suitability. Methods and results: We stained nuclei of confluent human umbilical vein endothelial cells with Hoechst33342 prior to induction of an artificial scratch wound. Treatments with various growth factors and several concentrations of nintedanib were performed to microscopically evaluate impacts on wound closure. We developed 2 tools for automated analysis of wound closure image sets. Utilizing cell-free area measuring or cellular density evaluation, respectively, migration behavior was assessed well-wise for each time point. We identified pro-migratory effects of interleukin 1β as well as inhibitory actions of nintedanib. Hoechst33342 staining allowed for cell counting which was excluded as a contributing factor to wound closure in our assay. Conclusion: We developed a cost-effective, high-throughput pipeline for monitoring cell migration in vitro. We believe that our protocol will accelerate pre-clinical screenings not only for medications targeting endothelial wound closure but also drug discovery research in a broad range of diseases involving cellular migration.